THE EFFECTIVENESS OF QUANTUM TEACHING MODEL WITH POWER POINT MEDIA LINKED VIDEO OF NATURAL EVENTS ON NEWS WRITING SKILL LEARNING BY GRADE X STUDENTS OF SMK SWASTA MUHAMMADIYAH 04 MEDAN - Abdullah Hasibuan; Nirmawan Nirmawan; Yugi Diraga Prawiyata (Sensei International Journal of Education and Linguistic, 2021)
In the process of obtaining science, there are factors that need to be improved, namely the learning process. Education should not override the learning process because in a learning process will create an environmental system that instructs students so that teaching objectives can be achieved optimally. It is otivated by the low ability of students in writing news. This is due to the difficulty of students in understanding when explaining the material in front of the class, which the difficulty to understand the words contained in the news. The objective of the research was to explain the use of Quantum Teaching learning model in improving skill to write news by grade X students of SMK Swasta Muhammadiyah 04 Medan. The data collected in this research was to use a test of the ability to write news with quantum teaching learning model. This research method was an experimental method could be interpreted as a research method used to find the effectiveness of actors on others in controlled conditions. The external and expected achievement targets of this research were scientific publications in the journal of Metamorfosa and Teaching Books